2010
DOI: 10.3109/00498254.2010.492879
|View full text |Cite
|
Sign up to set email alerts
|

Disposition of bazedoxifene in rats

Abstract: Bazedoxifene acetate (BZA), a novel selective estrogen receptor modulator, is currently being developed for the prevention and treatment of osteoporosis in post-menopausal women. In this study, the disposition of BZA was determined in the rat, a pharmacology and safety model. After a single 0.2 mg/kg intravenous (IV) administration to ovariectomized female rats, the plasma clearance (3.9 L/h/kg) and volume of distribution (16.8 L/kg) of BZA were high and the elimination half-life was short (3.8 h). The bioavai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…Both BZA and E 2 were dissolved in dimethyl sulphoxide (1 mg mL ‐1 stock). These protocols give plasma concentrations of 20.7 ± 2.1 ng mL ‐1 for BZA and 45.6 ± 7.8 pg mL ‐1 for E 2 , which closely fit those reported in other studies for both BZA and E 2 …”
Section: Methodssupporting
confidence: 88%
“…Both BZA and E 2 were dissolved in dimethyl sulphoxide (1 mg mL ‐1 stock). These protocols give plasma concentrations of 20.7 ± 2.1 ng mL ‐1 for BZA and 45.6 ± 7.8 pg mL ‐1 for E 2 , which closely fit those reported in other studies for both BZA and E 2 …”
Section: Methodssupporting
confidence: 88%
“…For this analysis, animal lung concentration data were available for anidulafungin (rat), bazedoxifene (rat), chloroquine (3 albino rat studies), favipiravir (monkey), hydroxychloroquine (2 albino rat studies), nitazoxanide (mouse), tamoxifen (rat), cyclosporine (rat), ritonavir (rat), azithromycin (mouse), dolutegravir (mouse), gilteritinib (albino rat), and lopinavir (rat). [23][24][25][26][27][28][29][30][31][32] Agreement between the predicted and measured K p was assessed by simple linear regression and by constructing Bland-Altman plots, the limits of agreement (mean ± 2 SD) were included in these plots as previously described. 33…”
Section: Data Analysis and Interpretationmentioning
confidence: 99%
“…1 A ). Studies in rats have shown that the half-lives of these SERMs are 13.5 h for Ral ( 11 ), 9.4 h for Las ( 41 ), and 3.8 h for Bza ( 10 ). The substances were given once/day, 5 days/wk, for 3 wk.…”
Section: Methodsmentioning
confidence: 99%